PEMANFAATAN LIMBAH CANGKAN TIRAM UNTUK MEMURNIKAN BIOGAS DARI PENGOTOR KARBON DIOKSIDA - Nindhia, T.G.T.; Surata, I.W.; Antara, R. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
For the reason of health, many of livestock activity in Bali already have the anaerobic digester unit for processing waste of livestock and produce fertilizer and biogas. One of the main impurity in the biogas is Carbon dioxide (CO2). that quite difficult to eliminate from the biogas. Some commercial product that available in the market recently are guit complicated and consume hight cost in practical. For this reason it is needed to develop simple method to purify biogas form CO2 impurity so that can be applied as appropriate technology for addressed community. In this community service was develop method of carbon dioxide removal (CDR) to purify biogas from CO2 impurity. A waste of clam shell from seafood restaurant around jimbaran , Bali,Indonesia was collected for this purpose and then burn to become quicklime and after that react with water to obtain slaked lime. The slaked lime then was extruded to become half dry pellet by extrusion continued with drying in a isolated chamber to avoid reaction with CO2 from the air. This technique able to reduce CO2 from biogas to a optimum level so that the biogas is free from CO2 impurities